High-resolution study of planetesimal formation by gravitational collapse of pebble clouds - Polak, Brooke; Klahr, Hubert (The astrophysical journal, 2023)
Planetary embryos are built through the collisional growth of 10-100 km-sized objects called planetesimals, a formerly large population of objects, of which asteroids, comets, and Kuiper Belt objects represent the leftovers from planet formation in our solar system. Here, we follow the paradigm that turbulence created overdense pebble clouds, which then collapse under their own self-gravity. We use the multiphysics code GIZMO to model the pebble cloud density as a continuum, with a polytropic equation of state to account for collisional interactions and capturing the phase transition to a quasi-incompressible “solid” object, i.e., a planetesimal in hydrostatic equilibrium. Thus, we study cloud collapse effectively at the resolution of the forming planetesimals, allowing us to derive an initial mass function for planetesimals in relation to the total pebble mass of the collapsing cloud. The redistribution of angular momentum in the collapsing pebble cloud is the main mechanism leading to multiple fragmentation. The angular momentum of the pebble cloud and thus the centrifugal radius increases with distance to the Sun, but the solid size of the forming planetesimals is constant. Therefore we find that with increasing distance to the Sun, the number of forming planetesimals per pebble cloud increases. For all distances, the formation of binaries occurs within higher hierarchical systems. The size distribution is top-heavy and can be described with a Gaussian distribution of planetesimal mass. For the asteroid belt, we can infer a most likely size of 125 km, all stemming from pebble clouds of equivalent size 152 km.
Gesehen am 15.11.2023